Teacher’s scaffolding moves in communication strategies in secondary school EFL classes - Usadiati, Wahyu (citeus, 2010)
Teachers have their own strategies in communicating their messages in EFL classes. The strategies may be in the form of verbal and nonverbal signals to get the message through to the students. The results of the study show that scaffolding moves were mostly used by the teacher, consisting of organizing and maintaining student’s interest and motivation, modeling, code switching, explaining or elaborating, eliciting student’s response, checking student’s comprehension, and providing wait time. Non-verbal signals always occur for the accompaniment of the verbalization of the teacher’s messages.